Deformation and ballistic performance of conical aluminum projectiles impacting thin aluminum targets: Influence of apex angle. (December 2017) - Vijayan, Vijeesh; Hegde, S.; Gupta, N.K.
Highlights: Projectile deformation mode and Ballistic limit velocity is seen to be influenced by the apex angle of conical projectiles at low impact velocities. Projectile tip instability is shown to occur in the initial phase of contact, further leading to very brief dwell phase, in case of tip-flattening projectiles. Tip stability improves with apex angle while perforation ability decreases due to change in local failure mode of target. Experimental evidence for projectile entrapment mode of projectile defeat has been included. Abstract: Mechanisms of projectile defeat and ballistic resistance of thin targets impacted by tip-deformable conical projectiles have been discussed in the context of the influence of apex angle of the projectile. Transition in target local failure modes occurred as the projectile apex angle was altered. The effect on projectile deformation and ballistic properties has also been discussed. A brief discussion on projectile deformation mechanism and projectile defeat near ballistic limit velocities with supporting experimental evidence is included. Numerical simulation using ABAQUS/Explicit has been able to effectively predict the projectile deformation and associated target behavior.